2014
DOI: 10.1089/apc.2013.0329
|View full text |Cite
|
Sign up to set email alerts
|

Abuse and Resilience in Relation to HAART Medication Adherence and HIV Viral Load Among Women with HIV in the United States

Abstract: Abuse is highly prevalent among HIV + women, leading to behaviors, including lower adherence to highly active antiretroviral therapy (HAART) that result in poor health outcomes. Resilience (functioning competently despite adversity) may buffer the negative effects of abuse. This study investigated how resilience interacted with abuse history in relation to HAART adherence, HIV viral load (VL), and CD4 + cell count among a convenience sample of 138 HIV + women from the Ruth M. Rothstein CORE Center/Cook County … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 70 publications
1
91
1
1
Order By: Relevance
“…4,5 These factors may negatively affect health outcomes in myriad ways, including decreased engagement in HIV care, 6 and reduced adherence to medications. 7,8 An estimated 8% of HIV-positive people in the US abuse alcohol, 9,10 while onethird of HIV patients receiving care report active drug use. 10 Both alcohol and drug abuse are associated with poor ART adherence and viral suppression failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 These factors may negatively affect health outcomes in myriad ways, including decreased engagement in HIV care, 6 and reduced adherence to medications. 7,8 An estimated 8% of HIV-positive people in the US abuse alcohol, 9,10 while onethird of HIV patients receiving care report active drug use. 10 Both alcohol and drug abuse are associated with poor ART adherence and viral suppression failure.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Approximately 55% of women living with HIV/AIDS have experienced intimate partner violence (IPV). 13 A history of trauma, abuse, and violence for HIV-infected women is associated with decreased medication adherence, 9,11,12 and increased viral load. 13,14 Studies consistently document high prevalence of mental health disorders and symptomatology among HIV positive populations.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have reported that positive and healthy decisions and actions stem from an initial development of a positive attitude towards life, acceptance of one's HIV/AIDS situation, generating meaning out of it, and being optimistic and these are related to better health outcomes (Dale et al, 2014). This stands true of Indigenous men in this study, many of whom also extend this positive attitude to a form of "pride culture" in their day-today lives.…”
Section: Resiliencementioning
confidence: 59%
“…In two recent studies with women living with HIV/AIDS, resilience in those who had sexual abuse history was shown to potentially promote better adherence to HAART, to decrease the viral load and slow down CD4 + cell count decline rates (Dale et al, 2014;Ickovics et al, 2006). This finding was attributed to positive psychological factors exhibited by the study participants.…”
Section: Resiliencementioning
confidence: 91%
See 1 more Smart Citation